Are they accurate? Recruiters' personality judgments in paper versus video resumes. (August 2017) - Apers, Catherine; Derous, Eva
Abstract: Whether recruiters accurately infer personality from resumes is currently a topic of great interest in the light of technological advancements and new types of resume formats (like video resumes) that are increasingly being used. Based on predictions from the realistic accuracy model and the media richness theory, we investigated whether real recruiters ( N  = 296) are able to infer applicants' Big Five personality characteristics more accurately from video and audio resumes than from less information-rich resume formats (like paper resumes) and whether applicants' perceived attractiveness (physical/vocal) affects accuracy judgments. As expected and with the exception of extraversion, personality was not accurately judged from paper resumes. Interestingly, information-rich resume formats and applicants' perceived attractiveness did not affect accuracy judgments. Despite recruiters' stubborn reliance on their capacity to infer personality from resume information, study findings clearly showed that different types of resumes –also the new, more information-rich ones– are no valid tools to infer candidates' personality from. Highlights: New types of resume formats (video resumes) emerge and become increasingly popular. Whether recruiters accurately infer personality from resumes is under-researched. Personality judgments should be more accurate when applicants use a video resume. Results show that 'richer' resume formats do not lead to more accurate judgments. Resumes (incl. video resumes) are no valid tools to infer applicants' personality.